Project Feasibility Study on Fiber Concrete Roof (FCR) Tiles - Buensalida, Evelyn Marable (College of Engineering, 1994)
This is a study on the feasibility of establishing a manufacturing set-up for Fiber Concrete Roof tiles or FCR tiles. FCR tiles are essentially roof tiles similar to concrete roof tiles. FCR tiles are composed of sand, cement, water and fiber. It is the fiber content which differentiates FCR from a regular concrete tile. Fiber acts to increase the impact strength of the tile which makes it a better alternative to concrete tiles. This study was undertaken in conjunction with the UP Building Research Center's aim to push FCR as a viable roofing alternative in the Philippines today. There are three major parts in this feasibility study. These are the market study, technical study, and financial study. The market feasibility study was able to identify roofing needs of the country from which a market share of 24% in the first year of operation was determined. The volume of the production based on the market share was such that it is feasible to put up a plant. Further research showed that there are only 4 other FCR manufacturers, all small scale, of which only one is located in Metro Manila. Results of an informal poll and research in government agencies (such as NCSO, DTI etc.) served to support the feasibility of the market study. The technical study was able to pinpoint the actual plant site (in Kalookan) and the appropriate layout for the production process required. It also contains the number of workforce required (5 laborers) and the number of required machines (2 vibrating machines) at the first year of operation. After consideration of all of these a production cost figure of P 3.47/tile was arrived at. Comparison of this price with the competitors' prices show that FCR could indeed be marketed at a lower price which makes it technically feasible. The financial study contains the total project cost at start-up in the amount of P 3.6M. Of the possible sources of financing, an SSS loan plus the private financing would be the source of the source of the start-up capital. The financial study also includes Income statements, cash flow statements and balance sheets for the 5 years of operation. Ratios are also included in the evaluation of the different aspects of the profitability of the company. The first year of operation yields a positive cash flow and positive profit which would support the feasibility of the proposed project.